(untitled) (Third Sector Social Economic Review, 2023)
Today, many businesses seek ways to persuade consumers to choose their brands for similar purchases. For this reason, it prioritizes sponsorship activities to add value to its products and services, be effective and permanent in the consumer’s mind, and be ahead of its competitors. The sponsorship activity, which is carried out in order to be effective in the minds of the consumer by indirectly making brand awareness provides in-kind or cash resources to the activities that support thebusiness’s goals by providing the purchase of products and services as well as brand awareness and corporate image. Businesses examineing to scrutinize give more importance to promotional activities to retain these people. The study aims to conduct a field study to determine the extent of the effect of the sponsorship activities on the consumer’s purchasing behavior in Ankara province. Data were obtained by applying a face-to-face questionnaire from created in this study, using quantitative research methods. A total of 430 questionnaires were collected and the hypotheses created were analyzed with the SPSS 22.0 statistical program. As a result of the questionnaires, Anova was evaluated using t-test, Sobel test and correlation analysis tests as descriptive statistics. It has been concluded that the sponsorship activities affect the consumer’s purchase and that there is a significant relationship between them. This situation should be evaluated in the sense that it causes a positive effect on the subconscious of the consumer. These results will be a qualified guide for future research with marketing managers.